2010
DOI: 10.1007/s11664-010-1191-7
|View full text |Cite
|
Sign up to set email alerts
|

Growth of HgTe Quantum Wells for IR to THz Detectors

Abstract: We zone-engineered HgCdTe/HgTe/HgCdTe quantum wells (QWs) using the molecular-beam epitaxy (MBE) method with in situ high-precision ellipsometric control of composition and thickness. The variations of ellipsometric parameters in the w-D plane were represented by smooth broken curves during HgTe QW growth with abrupt composition changes. The form of the spiral fragments and their extensions from fracture to fracture revealed the growing layer composition and its thickness. Single and multiple (up to 30) Cd x H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
20

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(96 citation statements)
references
References 32 publications
1
75
0
20
Order By: Relevance
“…Нанофизика и наноэлектроника" 1617 ричесим контролем состава и толщины слоев [14,15]. Как показано в работах [14,15], данный подход, развитый лишь относительно недавно, позволяет контролировать толщину КЯ вплоть до одного монослоя.…”
Section: международный симпозиум "unclassified
See 1 more Smart Citation
“…Нанофизика и наноэлектроника" 1617 ричесим контролем состава и толщины слоев [14,15]. Как показано в работах [14,15], данный подход, развитый лишь относительно недавно, позволяет контролировать толщину КЯ вплоть до одного монослоя.…”
Section: международный симпозиум "unclassified
“…Как показано в работах [14,15], данный подход, развитый лишь относительно недавно, позволяет контролировать толщину КЯ вплоть до одного монослоя. Квантовые ямы HgTe/CdHgTe обладают рядом уни-кальных свойств, обусловленных, в частности, тем, что при уменьшении ширины КЯ можно осуществить пере-ход от инвертированной зонной структуры (наследуемой в широких КЯ от объемного HgTe), к нормальной через возникающий при некоторой критической толщине КЯ " графеноподобный" закон дисперсии [16].…”
Section: международный симпозиум "unclassified
“…The concentration of charged impurities in these QWs can be about 10 14 -10 16 cm -3 [6,7,16]. Due to the inverted band scheme and high density of states for heavy holes, the Fermi level lies higher than the bottom of the conduction band in the well.…”
Section: Band Scheme and Properties Of Qwmentioning
confidence: 99%
“…Photoluminescence [4,5] and photoconductivity [6] of Hg 1-x Cd x Te QWs grown on different substrates (Si, GaAs, ZnTe, CdTe) have been studied. It is shown in [7] that high-quality HgTe QW structures can be used for all-electric detection of radiation ellipticity in a wide spectral range, from far-infrared to mid-infrared wavelengths. Measurements of electrical conductivity, the Hall coefficient, and photoluminescence of ion-milled Hg 1-x Cd x Te films were performed in [8].…”
Section: Introductionmentioning
confidence: 99%
“…14 Optical conductivity of HgTe/CdTe QWs has long been an interesting topic since the tunable band gap can give rise to optical response in the terahertz-far infrared regime, a technologically important frequency window. Optoelectronic devices such as THz detectors and emitters 15,16 have applications in many areas of science and industry. It has been demonstrated that HgTe/CdTe superlattices have significant non-linear optical properties such as large v (3) , THz response, and high saturation threshold.…”
mentioning
confidence: 99%